Multiperson-CDS: framework multipropósito e personalizável baseado em ontologia para o apoio à decisão clínica - Pizzol, Diego Santos de Andrade (2011)
Over and over health organizations are attracted by the benefits from the process of automation in health care through information technology, such as speed, accuracy, security, control and economy. Evidenced in recent years by the effort increas-ing of several countries for the development of projects that aim to leverage the use of information technology in health. Nevertheless, there is no standard, nor a set of stan-dards, to solve guaranteed all the problems of health organizations, due to the complexi-ty of the health field and the inherent discrepancies in each one of them. In addition, the use of electronic health record alone ensures only improvement on accessibility and rea-dability of information. To achieve satisfactory levels of patient safety, quality in health care, increasing efficiency and reducing the cost, it is necessary to use a clinical decision support system. Although it is notorious its relevance and there are several solutions us-ing clinical decision support, only few implementations for the clinic routine have achieved significant results in relation to improving results and procedures in health. The MultiPersOn-CDS aims to solve this problem through an extendible and customiz-able framework that enables, through the use of ontologies, the development of specia-lized contextual agents to support clinical decision making with a focus on clinical care and in the workflow of professional health, adressed mainly at improving the health care. For the construction and validation of MultiPersOn allows the creation of multi-purpose agents of clinical decision support, able to adapt to the inherent changes in the health field, making possible the dissemination of these agents by health organizations due to greater simplicity of make changes and customizations in the framework. As a result, efforts can then be concentrated on building clinical decision support agents, without worrying about the adequacy of them with applications, thus trying to reduce the technological barriers to the use and dissemination of clinical decision support tools in electronic health record.